Pengaruh Motivasi Mengajar, Kepemimpinan Kepala Sekolah, dan Ketersediaan Sarana Prasarana Terhadap Kinerja Guru Sekolah Dasar - Widiyanti, Tri; Yulaeha, Siti; Hidayah, Zainur (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Based on the evidence of the results of the education report card on the performance of elementary school teachers in the Secang District, Magelang Regency, there are several recommendations for improvement in the form of principal policies related to matters of motivation, leadership, and school infrastructure to be improved. This study is to determine the effect of teaching motivation, principal leadership, and availability of infrastructure facilities on teacher performance, which can be used as a study material for related parties in determining the right strategy to improve the quality of primary school teacher performance. The method used This type of research uses a quantitative approach with a survey method. The results of this study found: (1) there is a positive and significant influence of teaching motivation on teachers‘ performance; (2) there is a positive influence between principals’ leadership on teachers‘ performance; (3) there is a positive and significant influence between the availability of infrastructure facilities and teachers’ performance; and (4) there is an influence between work motivation, principals' leadership, and the availability of infrastructure facilities together have a positive and significant influence on the performance of primary school teachers in Secang sub-district.